Eliminating Safe Havens for Transnational Cybercrimes in the African Continental Free Trade Area (Journal of Intellectual Property and Information Technology Law (JIPIT), 2022)
The continuous advancement in technology makes cybercrimes effortlessly transnational. Existing literature reveals that the inadequacies of cybercrime-specific legislations, procedural powers, and enforceable mutual legal assistance provisions constitute jurisdictional challenges to the prosecution of transnational cybercrimes (TNCCs). This paper appraises the adequacy of legal responses to jurisdictional challenges of TNCCs in the African region, especially the African Union Convention on Cyber Security and Personal Data Protection (the Malabo Convention). It argues that the presence of states without substantive or procedural laws on cybercrimes, or both, constitutes safe havens that challenge the effectiveness of such laws in states where they are present. It finds that the Malabo Convention has the potential to be a tool for eliminating safe havens in the African region and given the inter-connection between trade and TNCCs, it suggests that it could be made operational through its annexation as one of the protocols to the African Continental Free Trade Area (AfCFTA) Agreement. The author concludes that purely domestic legal responses to cybercrimes are inadequate and suggests a holistic approach through the operationalization of an effective regional instrument as a way to diminish safe havens for TNCCs in the African region.